The idea of progress in the experience of academic philosophy in Ukraine the second half of the 19th and early 20th centuries - V. G. Napadysta, (Ukrainian Cultural Studies, 2020)
The article analyzes the views of representatives of academic philosophy in Ukraine in the second half of the 19th and early 20th centuries on progress, its components, sources, driving forces and practical consequences of its implementation. It is determined that the topic of progress belonged to the topical issues of academic philosophizing in Ukraine of this period.Among the personalities interested in the idea of progress, the thoughts of S. S. Hohotskyi, M. Ya. Hrot, M. O. Olesnytskyi and H. I. Chelpanov attract attention. The most detailed idea of progress is presented in the creative work of the theologian-moralist M. O. Olesnytskyi, who saw in progress the unity of scientific, technical and moral progress. The signs of progress, in his opinion, were the growing power of the human spirit over nature, the strengthening of integration processes of spiritual orientation in relations between peoples and nations on the basis of the growing importance of the individual.For the views of academic philosophers in Ukraine in the second half of the 19th – early 20th century on the problems of historical progress, differing in the scope of detailed analysis of the diversity of the idea of progress, there is a common motive, which with certain interpretations is that the progressive development of humanity can be considered only in the unity of material, economic, scientific and technological development, moral improvement of personality, which is the dominant, leading force in this process.In academic philosophy in Ukraine in the second half of the 19th and early 20th centuries we do not find the dominance of an unambiguous understanding of the theory of progress as mainly material and technical, social improvement, based on quantitative arguments. In general, opinions were articulated on the interdependence of material, technical and spiritual components in the process of progress, the main purpose of which was determined by the moral improvement of man.
Keywords: academic philosophy, progress, scientific and technical progress, moral progress, moral improvement of the person